LDPC coding proposal for pulsed-OFDM modulation for WPAN systems using UWB communication in indoor propagation channels. (1st January 2012) - Manimegalai, C.T.; Kumar, R.; Babu S.B., Sumith
In this paper, we describe a combined approach where low density parity check ( LDPC ) codes are used to reduce the complexity and power consumption of pulsed orthogonal frequency-division multiplexing ( pulsed-OFDM ) ultra-wideband ( UWB ) systems. The proposed system will use LDPC codes to achieve higher code rates without using convolution encoding and puncturing thereby reducing the complexity and power consumption of pulsed-OFDM system. The LDPC-pulsed-OFDM system will achieve channel capacity with different code rates and will have good performance in different channel fading scenarios. The proposals from pulsed OFDM system is used where pulsed signals could spread the frequency spectrum of the OFDM signal. The performance of LDPC-pulsed-OFDM system for wireless personal area networks ( WPAN ) is analysed for different UWB indoor propagation channels ( CM3 and CM4 ) provided by the IEEE 802.15.3a Standard activity committee. To establish this, we present a design of LDPC-pulsed-OFDM system using the digital video broadcasting-satellite-second generation ( DVB-S2 ) standard and provide the simulation results for the different code rates supported by LDPC codes.